Drug and cell type-specific regulation of genes with different classes of estrogen receptor beta-selective agonists. - Sreenivasan Paruthiyil; Aleksandra Cvoro; Xiaoyue Zhao; Zhijin Wu; Yunxia Sui; Richard E Staub; Scott Baggett; Candice B Herber; Chandi Griffin; Mary Tagliaferri; Heather A Harris; Isaac Cohen; et al. (PLoS ONE)
Estrogens produce biological effects by interacting with two estrogen receptors, ERalpha and ERbeta. Drugs that selectively target ERalpha or ERbeta might be safer for conditions that have been traditionally treated with non-selective estrogens. Several synthetic and natural ERbeta-selective compounds have been identified. One class of ERbeta-selective agonists is represented by ERB-041 (WAY-202041) which binds to ERbeta much greater than ERalpha. A second class of ERbeta-selective agonists derived from plants include MF101, nyasol and liquiritigenin that bind similarly to both ERs, but only activate transcription with ERbeta. Diarylpropionitrile represents a third class of ERbeta-selective compounds because its selectivity is due to a combination of greater binding to ERbeta and transcriptional activity. However, it is unclear if these three classes of ERbeta-selective compounds produce similar biological activities. The goals of these studies were to determine the relative ERbeta selectivity and pattern of gene expression of these three classes of ERbeta-selective compounds compared to estradiol (E(2)), which is a non-selective ER agonist. U2OS cells stably transfected with ERalpha or ERbeta were treated with E(2) or the ERbeta-selective compounds for 6 h. Microarray data demonstrated that ERB-041, MF101 and liquiritigenin were the most ERbeta-selective agonists compared to estradiol, followed by nyasol and then diarylpropionitrile. FRET analysis showed that all compounds induced a similar conformation of ERbeta, which is consistent with the finding that most genes regulated by the ERbeta-selective compounds were similar to each other and E(2). However, there were some classes of genes differentially regulated by the ERbeta agonists and E(2). Two ERbeta-selective compounds, MF101 and liquiritigenin had cell type-specific effects as they regulated different genes in HeLa, Caco-2 and Ishikawa cell lines expressing ERbeta. Our gene profiling studies demonstrate that while most of the genes were commonly regulated by ERbeta-selective agonists and E(2), there were some genes regulated that were distinct from each other and E(2), suggesting that different ERbeta-selective agonists might produce distinct biological and clinical effects.